Evaluating animations as student aids in learning computer algorithms - Byrne, Michael D.; Catrambone, Richard; Stasko, John T. (Computers and education, 1999)
We conducted two experiments designed to examine whether animations of algorithms would help students learn the algorithms more effectively. Across the two studies we used two different algorithms — depth-first search and binomial heaps — and used two different subject populations — students with little or no computer science background and students who were computer science majors — and examined whether animations helped students acquire procedural and conceptual knowledge about the algorithms. The results suggest that one way animations may aid learning of procedural knowledge is by encouraging learners to predict the algorithm's behavior. However, such a learning improvement was also found when learners made predictions of an algorithm's behavior from static diagrams. This suggests that prediction, rather than animation per se, may have been the key factor in aiding learning in the present studies. These initial experiments served to highlight a number of methodological issues that need to be systematically addressed in future experiments in order to fully test the relationship between animation and prediction as well as to examine other possible benefits of animations on learning.